2021
DOI: 10.1097/md.0000000000026633
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tapered endotracheal tube cuff pressure after changing position to hyperextension of neck

Abstract: Background: Endotracheal tube (ETT) with a tapered-shaped cuff had an improved sealing effect when compared to ETTs with a conventional cylindrical-shaped cuff. Positional change and neck movement typically displace an ETT and change the intracuff pressure. The aim of the current study was to compare the ETT cuff pressure in the TaperGuard ETT vs the conventional ETT after a change from the supine, neutral position to the extension of the neck and semi-Fowler position for thyroid surgery.Methods: This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Other investigators have reported a larger increase in tapered cuff pressures than in cylindrical cuff pressures after neck extension, rotation, or change of position ( 16 18 ). Differences in study design, including the site or type of surgery and the selection of baseline pressures, likely explain the unique findings of different studies.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Other investigators have reported a larger increase in tapered cuff pressures than in cylindrical cuff pressures after neck extension, rotation, or change of position ( 16 18 ). Differences in study design, including the site or type of surgery and the selection of baseline pressures, likely explain the unique findings of different studies.…”
Section: Discussionmentioning
confidence: 88%
“…extension, rotation, or change of position (16)(17)(18). Differences in study design, including the site or type of surgery and the selection of baseline pressures, likely explain the unique findings of different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that N2O diffusion in the cuff inflated with air may result in tracheal mucosal erosion and sore throat perioperatively [16]. Hyperextension of the neck has also been shown to increase ETT cuff pressure [17]. This is an important consideration in surgeries that require fixation of the head such as ear, nose, and throat, and neurosurgeries.…”
Section: Discussionmentioning
confidence: 99%